Kelas pranikah dan prakonsepsi untuk pencegahan stunting pada sekolah pranikah - Runjati Runjati; Ida Ariyanti; Umaroh Umaroh; Rr Sri Endang Pujiastuti; Mundarti Mundarti; Wan Ismahanisa Ismail (JURNAL INFO KESEHATAN, 2025)
Stunting is a growth disorder of children under five due to malnutrition, with the prevalence rate in Indonesia in 2023 reaching 21.5%. To reduce stunting rates, premarital and preconception classes are essential in providing knowledge and skills to prospective parents to prevent stunting. This study aims to develop an intervention module for premarital and preconception classes that integrates education on stunting prevention with coping skills training. The study also seeks to measure the effects of the module on participants’ perceived stress, coping skills, and self-efficacy, as part of an effort to strengthen the preparedness of prospective brides in maintaining maternal and child health and preventing stunting. This study is a quasy experimental study with a one-group pretest-posttest design. The population in this study were women in the premarital and preconception period. The sampling technique used was probability sampling, a simple random sampling of 41 people—data analysis using the Wilcoxon Test. The study results showed significant differences in three variables after the premarital class intervention. The stress perception scale experienced a decrease in mean score from 20.93 to 18.83 with a difference of -2.10 (p=0.002). Self-confidence experienced an average increase from 44.76 to 48.27 with a difference of 3.51 (p=0.002). Coping strategies also increased the average score from 97.34 to 99.24, with a difference of 1.90 (p=0.023). Premarital classes are effective in reducing stress and increasing self-confidence and coping strategies. Premarital classes and preconception programs with coping skills need to be expanded to prevent stunting.